Use of SGLT-2 Inhibitors in Acute Myocardial Infarction (CARDIOLOGY OF UZBEKISTAN, 2026)
Cardiorenometabolic syndrome (CRMS) is a multifactorial clinical condition reflecting complex and interrelated pathobiological processes involving the cardiovascular, renal, and metabolic systems. Its central mechanisms include visceral adiposity, insulin resistance, adipokine imbalance, chronic low-grade inflammation (metaflammation), and oxidative stress 1, 2. This pathological background contributes to the development of acute myocardial infarction (AMI) through endothelial dysfunction, reduced nitric oxide (NO) bioavailability, impaired microvascular perfusion, and destabilization of atherosclerotic plaques. In patients with CRMS, AMI differs from the classical ischemic model, as it is characterized not only by impaired coronary blood flow but also by an intense inflammatory response, activation of the immune system, and disturbances in cellular energy metabolism. During the early phase of infarction, damage-associated molecular patterns (DAMPs) activate Toll-like receptors, initiating the NF-κB signaling pathway and increasing the production of pro-inflammatory cytokines, including IL-1β, IL-6, and TNF-α. Furthermore, mitochondrial dysfunction and excessive generation of reactive oxygen species (ROS) amplify oxidative stress, promoting lipid peroxidation, DNA damage, and cardiomyocyte apoptosis. In recent years, sodium-glucose cotransporter-2 (SGLT2) inhibitors, particularly dapagliflozin, have attracted considerable attention as agents with broad cardiorenometabolic benefits. Their therapeutic effects are multifaceted and extend well beyond glycemic control. SGLT2 inhibitors exert cardioprotective effects by suppressing inflammatory signaling pathways (NF-κB and the NLRP3 inflammasome), reducing oxidative stress, restoring mitochondrial function, inhibiting the sodium-hydrogen exchanger-1 (NHE1), and decreasing intracellular calcium overload in cardiomyocytes 9, 12. This review systematically analyzes the role of SGLT2 inhibitors in the pathogenesis of AMI, their molecular, cellular, and systemic mechanisms of action, and their cardiorenometabolic efficacy based on evidence from contemporary clinical studies, including the DAPA-MI (Dapagliflozin in Myocardial Infarction) trial.